2021
DOI: 10.1002/nop2.791
|View full text |Cite
|
Sign up to set email alerts
|

Surgery decision conflict and its related factors among newly diagnosed early breast cancer patients in China: A cross‐sectional study

Abstract: According to global research data released by the World Health Organization (Bray et al., 2018), there were approximately 2.1 million newly diagnosed breast cancer (BCa) patients in 2018.In China, BCa accounts for 15% of all new female cancer cases and is still the most frequently diagnosed cancer in women (Chen et al., 2016). In addition to the high incidence rate of BCa, the survival rate is also increasing. In a survey conducted in 72 regions in China, the 5-year survival rate of BCa patients reached 58%-90… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 28 publications
0
9
2
Order By: Relevance
“…This was different from another study, which reported a high decision conflict of 45.68 (SD = 23.40) among women newly diagnosed with early stage breast cancer in China (Tang et al, 2021). In our study, women completed the surgery and adjuvant therapy, while in Tang's study, women were confronted with decisions regarding surgery (Tang et al, 2021). Women may feel more uncertainty about the trade‐offs of different types of surgery before decision‐making, while after the completion of surgery, they have to accept the treatment results, thus experiencing less decisional conflict.…”
Section: Discussioncontrasting
confidence: 87%
See 3 more Smart Citations
“…This was different from another study, which reported a high decision conflict of 45.68 (SD = 23.40) among women newly diagnosed with early stage breast cancer in China (Tang et al, 2021). In our study, women completed the surgery and adjuvant therapy, while in Tang's study, women were confronted with decisions regarding surgery (Tang et al, 2021). Women may feel more uncertainty about the trade‐offs of different types of surgery before decision‐making, while after the completion of surgery, they have to accept the treatment results, thus experiencing less decisional conflict.…”
Section: Discussioncontrasting
confidence: 87%
“…In our study, the decisional conflict of breast cancer survivors was 22.01 (SD = 17.36), which was mild. This was different from another study, which reported a high decision conflict of 45.68 (SD = 23.40) among women newly diagnosed with early stage breast cancer in China (Tang et al, 2021). In our study, women completed the surgery and adjuvant therapy, while in Tang's study, women were confronted with decisions regarding surgery (Tang et al, 2021).…”
Section: Discussioncontrasting
confidence: 87%
See 2 more Smart Citations
“…Besides, the decision-making progress were in uenced by family factors, traditional culture and fatalism [8]. When confronted with surgical decision, BC patients always experienced anxiety, illness uncertainty, depresses, hesitation and decision con ict [9].Facing numerous treatment options, BC patients experienced moods uctuate and always given the decision-making right to physicians, which just considered survival time and didn't consider patients' preference [10]. A survey showed 6-23% of cancer patients experience decision regret [11].…”
Section: Introductionmentioning
confidence: 99%